Aggressive FLC Escape in a Patient with IgD Myeloma - Farges, Cédric; Roussel, Murielle; Huynh, Anne; Blancher, Antoine; Puissant-Lubrano, Bénédicte (Case Reports in Hematology, 2015)
Background. Some patients who are stable or in remission from a myeloma secreting intact monoclonal immunoglobulin (+/− associated free light-chains (FLCs)) relapse with production of FLC. This FLC escape is one of the illustrations of the intraclonal heterogeneity of multiple myeloma. Results. We report FLC escape in a patient with IgD myeloma characterized by a severe outcome. We discuss parameters that negatively impacted prognosis in this patient, including bone lesions, biochemical parameters, and genomic abnormalities. Conclusion. This case illustrates the selective pressure exerted by therapeutic drugs and the variable sensitivity of subclones to these drugs; it also highlights the importance of FLC monitoring in treated MM patients.